2010
DOI: 10.1038/emboj.2010.255
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the transfer-messenger RNA as the ribosome resumes translation

Abstract: Visualizing the transfer-messenger RNA as the ribosome resumes translationBacterial ribosomes that are stalled on mRNAs lacking a stop codon can be rescued by a process called ‘transtranslation' that involves the ribonucleoprotein complex tmRNA–SmpB. This cryo-EM study, and the copublished study by Weis et al, reveal how translation on tmRNA is resumed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
49
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 44 publications
6
49
0
Order By: Relevance
“…A second possibility is that K 131 GKK affects the placement of the tmRNA template within the decoding center. We previously reported that SmpB plays a role in selecting the reading frame on tmRNA (Watts et al 2009), a finding later confirmed by structural studies (Fu et al 2010;Weis et al 2010). Residues Tyr24 and Ala130 were implicated in this process; mutation of these residues alters the reading frame on tmRNA.…”
mentioning
confidence: 53%
“…A second possibility is that K 131 GKK affects the placement of the tmRNA template within the decoding center. We previously reported that SmpB plays a role in selecting the reading frame on tmRNA (Watts et al 2009), a finding later confirmed by structural studies (Fu et al 2010;Weis et al 2010). Residues Tyr24 and Ala130 were implicated in this process; mutation of these residues alters the reading frame on tmRNA.…”
mentioning
confidence: 53%
“…Since trans-translation is missing in the eukaryotes, these drugs should have reduced side effects on the cells and metabolisms of the patient. 60,62 E-site translocation and ribosome exit. The model presented here lends support to a mechanism in which the next transition of tmRNA-SmpB from the P-to the E-site would follow the same dynamics (Fig.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…2d), especially those required for the transition from the A-to the P-site. 60,62 The translocation step implies dynamical motions of tmRNA-SmpB but also of the ribosome to (a) allow the complex to cross the hurdles between the A and P-sites (b) swap the mRNA templates (c) select the correct resume codon and maintain the reading frame on tmRNA.…”
Section: Rna Biology Volume 8 Issuementioning
confidence: 99%
“…These complexes are perhaps easier to form in vitro. However, as we discussed in our original publication, 31 the insertion of the MS2 hairpin in our tmRNA construct might have over-stabilized the helix 5 that contains part of the ORF, resulting in the vast majority of our in vivo-formed complexes being stalled at the resume state. Thus, to form the complex that depicts later stages of trans-translation in vivo, we could probably insert one or more codons into the single-stranded part of the ORF.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 97%
“…The cryo-EM structure of the tmRNA-ribosome complex in the resume state (the state in which the TLD has moved to the ribosomal P site and translation is ready to resume on the ORF of the tmRNA), obtained independently by our group and the Gillet group, addressed both of these questions. 19,31 The two structures, published back-toback, are from two different organisms, E. coli (our group) and T. thermophilus (the Gillet group). Our complex was formed in vivo.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%